High Fixation Failure Rate of Cephalomedullary Nail Fixation in Patients with Low-Energy Basicervical Femoral Fractures: Do We Need Extramedullary Reduction? - Chang-Jin Yon; Ki-Cheor Bae; Young-Hun Kim; Kyung-Jae Lee (Medicina)
Background and Objectives: A basicervical femoral fracture is a relatively uncommon type of proximal femoral fracture. However, as the proportion of proximal femoral fractures rises in conjunction with the aging of society, the absolute number of patients with basicervical femoral fractures is also increasing. Nevertheless, the optimal surgical methods for the treatment of basicervical femoral fractures remain a topic of debate. The aim of this study is to evaluate the failure rates of cephalomedullary nail fixation in basicervical femoral fractures based on reduction types. Methods: A retrospective analysis was conducted on 22 patients (22 hips) with AO/OTA 31-A1.2 hip fractures who had undergone treatment with a cephalomedullary nail (PFNA-II or Gamma-3) between March 2007 and February 2018. They were classified into three groups based on the reduction types: extramedullary (E), anatomical (A), or intramedullary (I). The intramedullary group included cases where the basicervical component was impacted into the medullary canal, while the extramedullary group comprised cases where the component was displaced beyond the medullary canal. The anatomical group consisted of specimens that exhibited complete anatomical reduction. This was determined by both the anteroposterior (AP) view and the lateral view using simple radiographs. Results: There were 13 patients (59.1%) in Group E and 9 patients (40.9%) in Group A. No patients were classified in Group I. Fixation failure occurred in four patients (18.1%, 4/22). In Group E, no patients exhibited fixation failure (0%, 0/13). In contrast, four patients in Group A demonstrated fixation failure (44.4%, 4/9). Group A exhibited a significantly higher incidence of fixation failure (0% vs. 44.4%, p =0.037) compared to Group E. Conclusion: In the treatment of low-energy basicervical femoral fractures with cephalomedullary nails, extramedullary reduction demonstrated a lower rate of fixation failure compared to anatomical reduction in this study. While definitive conclusions regarding its superiority cannot be drawn due to the limited sample size, extramedullary reduction may serve as a promising alternative to reducing the high fixation failure rate associated with this challenging fracture type.